Assessing the solid mass flow sensing behaviour through capacitive sensing technique - Tasnim, Rumana; Khan, Sheroz; Arshad, Atika (IEEE, 2017)
This paper presents an experimental investigation of the behavior of a biomass test material, wheat. Ground wheat grain is replicated as fine biomass base. The experiment is based on voltage application inside a capacitive sensor. This sensor allows the sensing of very small capacitive variation. The sensor is incorporated with an interface sensing circuit based on circular and semi-circular shaped electrode and modified capacitive bridge. Analysis of a particular material’s flow sensing behavior has been carried out by evaluating the measurement data and assessing conformity between experimentally obtained and simulated data.